Relevansi dasar-dasar pendidikan di era digital - Wafa, Ahmad Shiddiq Al (Maliki Interdisciplinary Journal, 2026)
The digital revolution has fundamentally transformed the educational landscape, raising critical questions about the continued relevance of classical educational foundations amid accelerating technological change. This article examines the tension between traditional pedagogical principles—character formation, critical thinking, and cultural value transmission—and the digital competency demands of the 21st century. Through a systematic literature review drawing on recent studies, including articles from the Maliki Interdisciplinary Journal (MIJ) of UIN Maulana Malik Ibrahim Malang, and educational policy in Indonesia and globally, this article argues that the relevance of foundational education lies not in choosing between tradition and technology, but in synergistically integrating them. Findings indicate that Generation Z and Alpha require strong foundations in literacy, numeracy, and character values as prerequisites for using technology ethically and meaningfully. The impact of AI on learning methods is analyzed critically alongside Indonesian contextual case studies. The article concludes with evidence-based policy recommendations to reform the national curriculum to meet the needs of learners in the digital age without sacrificing the essence of education.